Pulmonologist-Administered Balanced Propofol Analgosedation during Interventional Procedures: An Italian Real-Life Study on Comfort and Safety. (13th June 2022) - Maffucci, Rosalba; Maccari, Uberto; Guidelli, Luca; Benedetti, Lucia; Fabbroni, Roberto; Piccoli, Bruno; Bianco, Andrea; Scala, Raffaele
Abstract : Propofol-based sedation provides faster recovery than midazolam-based regimens with similar safety and comfort during video flexible bronchoscope (VFB) procedures. Pulmonologist-administered propofol "balanced" analgosedation (PAP-BAS) is still debated in Italy. In this real-life study, PAP-BAS safety and comfort during VFB procedures were investigated. We analysed prospectively the subjects undergoing elective VFB procedures in the Pulmonology and RICU of Arezzo Hospital between February and July 2019. PAP-BAS combined low propofol and meperidine doses titrated to achieve an RASS score between 0 and −3. The primary end-point was the complications' rate. Secondary end-points were as follows: the relation between propofol's dose and a subject's comfort assessed with a VAS, recovery time according to a modified Aldrete score ≥9, RASS, and subjects' will of undergoing the procedure again. We collected postprocedure symptoms' intensity too. Our 158 study patients (67 years; SD ± 14; 64% males) incurred in 25% of complication, fully resolved with medical therapy. Neither recourse to ventilator support nor death was reported. Intraprocedural comfort was good (94% of VAS score ≤2). Among postprocedural symptoms, cough was the most frequently reported, in 36% of the cases. Although half of subjects remembered the procedure, 90% of them would have repeated it, if necessary. 85% of them recovered from procedures within 10 minutes. Complications, VAS, and recovery time were not correlated with propofol dose. To our knowledge, this is the first Italian study showing that PAP-BAS to perform a VFB procedure is safe, well tolerated with a quick recovery. Randomised controlled trials are warranted to confirm these preliminary results.